How is social impact bonds model used by public sectors in impact investing in Finland? - Chen, Jianhong (2022)
This is a paper to look into how Social Impact Bonds model is used by public sectors in impact investing in Finland. Finland has made a number of impact investments to promote the nation’s well-being in different themes in the last decade.